Biology and biotechnology of actinobacteria - Wink, Joachim; Mohammadipanah, Fatemeh; Ham, Javad (Springer, 2017)
This book provides in-depth insights into the biology, taxonomy, genetics, physiology and biotechnological applications of Actinobacteria. It especially focuses on the latter, reviewing the wide variety of actinobacterial bioactive molecules and their benefits for diverse industrial applications such as agriculture, aquaculture, biofuel production and food technology. Actinobacteria are one of the most promising sources of small bioactive molecules and it is estimated that only a small percentage of actinobacterial bioactive chemicals have been discovered to date. Identifying new diverse gene clusters of biotechnological relevance in the genome of Actinobacteria will be crucial to developing advanced applications for pharmaceutical, industrial and agricultural purposes. The book offers a unique resource for all graduate students, researchers and practitioners in the fields of microbiology, microbial biotechnology, and the genetic engineering of Actinobacteria.